Third‐Grade fluid flow over a stretching sheet under Lorentz force and thermal radiation: Parametric continuation algorithm - Asiri, Fisal; Mumtaz, Mohd Aamir; Abbasi, Naveed sarwar; Haldar, Barun; Eshchanov, Temur; Sardor, Sabirov (Journal of Radiation Research and Applied Sciences, 2025)
In the current analysis, the energy and mass transmission subject to Lorentz force and thermal radiation through the third‐grade fluid across a stretching inclined sheet is considered. The thermal radiation, heat source, and magnetic impact are also applied to the fluid flow. The flow equations are reformulated into the non-dimensional form of ODEs using the similarity transformations. The lowest order of ODEs is solved through the PCM (parametric continuation method) by using Matlab software. For the validity of the results, the outcomes are compared to published studies. The relative percent error between the present calculation and the published is 0.00537 % at Pr = 10 (Prandtl number), which reveals that the present results are accurate. The nature of the flow constraints on the physical interest quantities, skin friction, velocity, and energy fields are displayed via Figures. For the validity of the results, for particular cases, the results are compared to the published study. It has been observed that the velocity field enhances for the intensifying values of the third-grade fluid parameter. The effect of the magnetic term and the permeability factor reduces the fluid velocity. The radiation effect and the heat source elevate the temperature field. The energy transfer rate enhances up to 15.46340 % by raising the buoyancy impact from 0.3 to 0.9, whereas the flow rate declines up to −12.4772 %.